PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) PADA MATERI BERPIKIR KOMPUTASIONALTERHADAP HASIL BELAJAR SISWA KELAS VIII DI MTS MUHAMMADIYAH 1 SAMARINDA - Priyandika; Galih Yudha Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Teams Games Tournament (TGT) learning model on students’ learning outcomes and responses in computational thinking material in class VIII-C of MTs Muhammadiyah 1 Samarinda. This research employed a quantitative approach with a pre-experimental design using a one group pretest-posttest design. The subjects of this study consisted of 37 students. Data collection techniques included tests (pretest and posttest) and student response questionnaires, while data analysis was conducted by calculating mean scores, N-Gain, and the percentage of student responses. The results showed an improvement in students’ learning outcomes, indicated by an increase in the average score from 75.95 in the pretest to 93.24 in the posttest. The N-Gain value of 0.58 was categorized as moderate with a fairly effective level. This improvement indicates that the implementation of the TGT model supported by question card media can help students better understand computational thinking material. In addition, the questionnaire results showed that students’ responses to the learning process were categorized as very positive, with a percentage of 89%. This indicates that students demonstrated high levels of interest, motivation, and engagement during the learning process. The use of question card media within the TGT model also contributed to creating a more active, interactive, and enjoyable learning environment. Therefore, the TGT learning model can be an effective alternative in improving students’ learning outcomes and responses in informatics learning, particularly in computational thinking material.